Studi Komparasi Jumlah Kasus Stunting Berdasarkan Status Penerapan STBM - Fatimah, Siti; Siwiendrayanti, Arum (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: Poor sanitation conditions have a negative impact on many aspects of life, such as decreasing of environmental quality, polluted drinking water sources and the emergence of diseases such as stunting nutrition problems. The purpose of this study was to determine the comparative difference in the number of stunting cases based on the status of the implementation of Community-Led Total Sanitation in Tegal Regency. Methods: This type of research uses a quantitative approach with a comparative method. The research subjects were 212 villages in Tegal Regency. Research variables include the status of CLTS implementation, access to sanitation and access to clean water. The instruments used are secondary data recapitulation forms and computers. The sampling technique used simple random sampling. Data were analyzed using the Mann Whitney test with = 0.05. Results: The average number of stunting cases is 67.85 cases based on STBM application status, 93.50 cases based on access to sanitation, and 83.43 cases based on access to clean water. Conclusion: There is a significant difference between the status of CLTS implementation (p=0.000), access to sanitation (p=0.000), access to clean water (p=0.000) and the number of stunting cases.